Analysis of EEG Signal for the Estimation of Concentration Level of Humans. Issue 1 (March 2021) - Velnath, R.; Prabhu, V.; Krishnakumar, S.
Abstract: Especially when studying or thinking, focus is an important part of our lives. To understand humans' concentration mechanism, the brain activity is monitored using EEG signals. Electroencephalogram (EEG) is test used to track and record the brain wave patterns based on the electrical activity of the brain. It is a very versatile tool for the detection of brain activity. Based on concentration and thinking the brain waves will get change due to their change in brain activity. The variations in brain waves are analysed and the features are extracted using various methods. EEG data are collected for different persons under two different age groups of 20 to 23 age and 29 to 31 aged people because the concentration varies with respect to age. The characteristics are extracted from the collected EEG signal using FFT, Mean, Standard Deviation (SD), Median and Mean Root Square. The concentration level is determined by comparing the extracted features for different aged individuals.